Pengaruh Konflik Peran dan Ambiguitas Peran Terhadap Komitmen Independensi Auditor Internal - Victorinus Laoli; Sonitehe Gea (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
This study aims to assess and identify the influence of role conflict and role ambiguity and the independence commitment of internal auditors to work at the Regional Development Bank of North Sumatra, Nias Islands Region. Determination of respondents is done by purposive sampling, which is a sampling technique based on certain criteria. The number of questionnaires distributed was 35 questionnaires. This study uses simple linear regression. The results of the analysis in this study indicate that the role conflict and the ambiguity of each affect.